2012
DOI: 10.1177/1363460711433735
|View full text |Cite
|
Sign up to set email alerts
|

More like a donor or more like a father? Gay men’s concepts of relatedness to children

Abstract: Lesbian mothers internationally have negotiated informal donor insemination arrangements with gay men since the earliest days of planned lesbian parenthood. In recent years, the relational status to children of these men has been subject to increasing legal and research scrutiny. In this article, based on interviews with Australian gay men, the various meanings of biological relatedness to children are explored from the men’s perspective. Of particular interest is the difference between a ‘donor’ and a ‘father… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
0
14
0
10
Order By: Relevance
“…While some children talk about this person as a man or a guy, others say seed-daddy or daddy. Previous studies have shown that a sharp distinction between fathers and donors is not always applicable, neither for the donors/fathers (Dempsey, 2012) nor for the children (Goldberg & Allen, 2013a;Vanfraussen et al, 2001). My denomination is therefore a simplification of a more complex issue, which suits the adult research discourse.…”
Section: Another Concept Frequently Used By the Participants And Mysementioning
confidence: 99%
“…While some children talk about this person as a man or a guy, others say seed-daddy or daddy. Previous studies have shown that a sharp distinction between fathers and donors is not always applicable, neither for the donors/fathers (Dempsey, 2012) nor for the children (Goldberg & Allen, 2013a;Vanfraussen et al, 2001). My denomination is therefore a simplification of a more complex issue, which suits the adult research discourse.…”
Section: Another Concept Frequently Used By the Participants And Mysementioning
confidence: 99%
“…Néanmoins, ces recherches apportent un éclairage important sur la conception assistée à l'aide d'un tiers alors que très peu de recherches ont documenté le point de vue d'hommes qui agissent comme donneurs de sperme (Dempsey, 2012 ;Riggs, 2008), la plupart se centrant plutôt sur les représentations qu'en ont les personnes bénéficiaires de leurs dons (Goldberg et Allen, 2009 ;Kelly, 2009 ;Ryan-Flood, 2005 ;Svab, 2007). Malgré le contexte spécifique relié aux dons entre particuliers qu'autorise la Loi instituant l'union civile et établissant de nouvelles règles de filiation, ces deux recherches sont, à notre connaissance, les seules qui se soient penchées sur le sujet au Québec.…”
Section: Resultsunclassified
“…Cela est d'autant plus important que les divergences de points de vue, nous le savons, exacerbent l'apparition de conflits entre les prota-I. Côté, K. Lavoie et F. de Montigny, « J'ai aidé deux femmes à fonder leur famille » : le don de gamètes entre particuliers en contexte québécois, Enfances Familles Générations, no 23, 2015, p. 127-147. www.efg.inrs.ca/index.php/ EFG/article/view/441 141 gonistes (Dempsey, 2012), ou encore peuvent être à la source d'une certaine détresse psychologique chez un donneur dont le rôle auprès des enfants ne convient pas à ses aspirations de départ (Riggs, 2008). Conformément à l'entente de départ et au regard de la trajectoire familiale, la propension des donneurs à se référer à l'unité parentale des mères pour la prise de décision concernant les enfants inhibe l'émergence de tensions ou de conflits entre les adultes.…”
Section: De La Procréation Assistée Par Autrui à La Procréation Négocunclassified
See 1 more Smart Citation
“…Elle insiste en particulier sur les hésitations des acteurs quant au statut de ce tiers de procréation : tantôt est-on tenté de voir en lui davantage qu'un simple pourvoyeur de matériel génétique, tantôt adhère-t-on à la nécessité de ne pas en faire une figure parentale concurrentielle dans un contexte social où l'exclusivité reste une des marques du lien entre parent et enfant. Bien que certaines sociologues aient commencé à examiner les diverses implications du recours à un donneur connu (Ryan-Flood, 2009;Dempsey, 2012), il reste encore de nombreuses pistes de recherche à approfondir en la matière.…”
Section: Les Enjeux En Suspensunclassified